Improving the pedagogy of islamic religious education in secondary schools: The role of critical religious education and variation theory - (:unkn) unknown (Taylor and Francis Inc., 2019)
This timely book focusses on the central issues and questions which emerge in relation to the teaching and learning of Islam in confessional and constructivist religious education. Considering the consequences of a lack of diversity in the Islamic Religious Education curriculum, the text also explores the challenges faced by Muslim pupils in connection with secularism and radical Islam. Through rich analysis of research carried out across Muslim and public secondary schools in the UK, this book develops a meaningful pedagogy of Islamic Religious Education. In particular, the volume investigates the benefits of Critical Religious Education and Variation Theory frameworks on student learning in Religious Education classrooms and illustrates how these didactic frameworks can help to ameliorate distinct problems seen across Islamic Religious Education. Chapters identify discrete pedagogical issues that arise in the confessional and constructivist approaches to Islamic Education, such as students' difficulties in relating to concept of Islam, and progressive approaches taken in public schools. In addressing these, the text proposes a new theoretical and pedagogical approach to the teaching of Islam, which draws on the philosophy of Critical Realism, the theories of Critical Religious Education, and Variation Theory. This book will be of great interest to postgraduate students, researcher scholars and academics in the fields of religion and education and Islamic studies. In addition, it will be of interest to social equity professionals and public policy decision makers. © 2020 Taylor & Francis. All rights reserved.